New Evidence of a Late Pleistocene Occupation on the Southern Slopes of the Alborz Mountains. (3rd April 2021) - Hariryan, Hamid; Heydari-Guran, Saman; Motarjem, Abbas; Ghasidian, Elham
ABSTRACT: Most of our knowledge on the Palaeolithic of the Iranian Plateau derives from a scientific focus on the Zagros Mountains. In recent years, several Palaeolithic research projects have been conducted in different parts of Iran, including southern piedmonts of the Alborz Mountains and the Iranian Central Plateau. Here, we present a Palaeolithic occupation in a rockshelter on the southern slopes of the Alborz Mountains. The Palaeolithic artefacts have been recovered from at least three looters' pits at the center of the rockshelter. The site is significant at least for two aspects: firstly, due to the fact that the southern slopes of the Alborz Mountains have not yet been identified for the Palaeolithic, the site provides unique data on the Iranian Plateau. Secondly, the location of the site, and the physiogeographic and lithic analyses of Sorheh are invaluable for the reconstruction of hominin behavior and settlement patterns in this under-researched area.